Pelatihan Media Pembelajaran guna Meningkatkan Kompetensi Mengajar Guru di SMP Negeri 3 Kutorejo - Rosyida Nurul Anwar; Putri Ayu Agusrini; Salsabila Tazkia Aulia (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
The development of science and technology in the world of education requires every individual to innovate. A teacher is a profession that requires particular skills in teaching students in schools. Developing skills in teaching is a must for teachers to get results that contribute to improving the quality of education. This service aims to provide understanding in the form of learning media training for teachers at SMP Negeri 3 Kutorejo. The implementation of community service activities regarding learning media training got satisfactory results because as many as 87% of teachers felt the benefits of increasing knowledge in teaching with learning media.